P component in the synovium in rheumatoid and osteoarthritis. Issue 6 (June 1988) - Butler, M G; D'Ardenne, A J; Scott, D L
Abstract : P component is present in amyloid deposits, normal serum, and normal tissues in relation to elastic fibres. Its pathological role in inflammatory synovitis was investigated. Its distribution was determined immunohistologically in 33 synovia: 15 rheumatoid; seven osteoarthritic; seven traumatic controls; and four infected biopsy specimens. P component was present in two circumscribed distributions: extracellular fibrils in dense fibroelastic tissue of the more fibrotic synovia; and in the arterial wall, where it was confined to a single elastic lamina in some cases and in others showed reduplication and fragmentation. These were not related to amyloid material. It shows no disease specificity, but P component categorises the nature of the pathological reaction and is typically in biopsy specimens showing the development of chronic fibrosis. There was close codistribution of P component with elastic tissue, though this was not absolute. P component had a different distribution from C reactive protein (in synovial lining cell layer), and fibronectin, which was absent from fibrotic areas. Understanding the pathological interactions of P component may help elucidate why some synovial reactions remain inflammatory and other progress to chronic fibrosis.